Identification and estimation of equivalent area parameters using synchronised phasor measurements. Issue 4 (1st April 2014) - Vahidnia, Arash; Ledwich, Gerard; Palmer, Edward; Ghosh, Arindam
Abstract : A new approach is proposed for obtaining a non‐linear area‐based equivalent model of power systems to express the inter‐area oscillations using synchronised phasor measurements. The generators that remain coherent for inter‐area disturbances over a wide range of operating conditions define the areas, and the reduced model is obtained by representing each area by an equivalent machine. The parameters of the reduced system are identified by processing the obtained measurements, and a non‐linear Kalman estimator is then designed for the estimation of equivalent area angles and frequencies. The simulation of the approach on a two‐area system shows substantial reduction of non‐inter‐area modes in the estimated angles. The proposed methods are also applied to a ten‐machine system to illustrate the feasibility of the approach on larger and meshed networks.